2020
DOI: 10.1021/acs.est.0c01503
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Transdermal Uptake of Phthalates and a Paraben from Cosmetic Cream Using the Measured Fugacity

Abstract: Transdermal uptake models compliment in vitro and in vivo experiments in assessing risk of environmental exposures to semi-volatile organic compounds (SVOCs). A key parameter for mechanistic models is a chemical driving force for mass transfer from environmental media to human skin. In this research, we measure this driving force in the form of fugacity for chemicals in cosmetic cream and use it to model uptake from cosmetics as a surrogate for condensed environmental media. A simple cosmetic cream, containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 118 publications
(254 reference statements)
0
2
0
Order By: Relevance
“…It was observed that pure liquid VOCs showed less permeability due to the dehydration of the stratum corneum. 104,105 Increased skin temperature enhances percutaneous absorption proportionally. In most studies, skin absorption measurements were conducted in temperature-controlled experiments.…”
Section: Skin-emitted Volatolomes and Their Association With Diseasesmentioning
confidence: 99%
“…It was observed that pure liquid VOCs showed less permeability due to the dehydration of the stratum corneum. 104,105 Increased skin temperature enhances percutaneous absorption proportionally. In most studies, skin absorption measurements were conducted in temperature-controlled experiments.…”
Section: Skin-emitted Volatolomes and Their Association With Diseasesmentioning
confidence: 99%
“…Concerns about toxic ingredients in cosmetics have recently increased. For example, heavy metals (HMs) are commonly combined with natural mineral pigments and artificial colorants to increase the brightness or color diversity . Although regulations regarding permissible levels of HMs (As, Cd, Hg, and Pb) in cosmetics have been issued in at least 69 countries, products with extremely high concentrations of restricted or unrestricted HMs are still commonly available.…”
Section: Introductionmentioning
confidence: 99%